Cohort effects on gender differences in alcohol use in the United States: How much is explained by changing attitudes towards women and gendered roles?. (September 2021) - Keyes, Katherine M.; Platt, Jonathan; Rutherford, Caroline; Patrick, Megan E.; Kloska, Deborah D.; Schulenberg, John; Jager, Justin
Abstract: Gender differences in binge drinking have converged in recent cohorts, due in part to faster decreases in consumption among boys in adolescence, and faster increases in consumption among women in young to middle adulthood. Changes in education and occupation explain a portion, but not all, of these differences; the present study examines how attitudes about gender, religion and family additionally explain cohort effects in binge drinking by sex. Data were drawn from the Monitoring the Future panel studies, including >54, 000 participants who were high school seniors from 1976 through 2006, followed to age 29/30 from 1988 through 2016. The main effect relationship between cohort and binge drinking was assessed, and 28 items on gender, religion and family were evaluated to determine if mediation criteria were met; mediation models assessed direct and indirect effects. Results indicated that gender, religion and family attitudes and beliefs among US adults across the 20 th and 21 st centuries have shifted dramatically but not monotonically. US adolescents and adults have largely become less religious; some attitudes on women and family have become less conservative and some more. Among men, views on marriage showed the largest mediation effects; agreeing with the statement 'one partner is too restrictive' mediated 3.35% of the cohort effect (95% C.I. 2.42, 4.31) and 'couples should live together before they are married' mediated 1.6% of the cohort effect (95% C.I. −2.37, −0.8). Among women, declines in religious service attendance mediated 2.0% of cohort effects in binge drinking (95% C.I. −3.03, −1.09), as well as similar family attitudes as men. In conclusion, changes in social roles, as well as some gender, and religious views, partially mediate cohort effects on binge drinking for men and women. The dynamic changes in how adolescents and adults view family and gender are important components of alcohol epidemiology. Highlights: US gender, religion family attitudes across the 20th and 21st centuries have shifted dramatically. Attitudes and beliefs mediate cohort trends in binge drinking among men and women. Dynamic changes in views about family are important components of alcohol epidemiology.